In vitro micropropagation of Rauvolfia serpentina (L.) Benth through induction of direct and indirect organogenesis - Bhadra, SK; Bhowmik, TK; Singh, P (Chittagong University Journal of Biological Sciences, 2013)
Leaf and nodal segments of two months old field grown seedlings of Rauvolfia serpentina (L.) Benth were aseptically cultured on agar solidified MS medium supplemented with various combinations and concentrations of auxins (NAA, IAA, 2,4-D and picloram) and cytokinins (BAP and Kn). The nodal segments produced highest number of multiple shoot buds (5.85/explant) on MS medium supplemented with 2.0 mgl-1 BAP + 0.2 mgl-1 NAA or 2.0 mgl-1 BAP + 0.1 mgl-1 IAA. Whereas nodal segment produced callus tissue of different nature on MS medium supplemented with 1.5 mgl-1 BAP + 0.5 mgl-1 IAA+ 1.5 mgl-1 2,4-D; 3.0 mgl-1 BAP + 1.0 mgl-1 NAA + 1.5 mgl-1 Kn and 0.1 mgl-1 Pic + 1.0 mgl-1 Kn. The callus tissue of light green and nodular nature on further subculture in a wide range of plant growth regulators (PGRs) supplemented media, differentiated into multiple shoot buds that underwent rapid elongation on 2.0 mg/l BAP and 0.2 mg/l NAA supplemented media. The elongated shoot buds on further subculture in rooting media produced strong and stout roots. Half strength MS with 1.5% (w/v) sucrose was most effective for enhancing rooting. Finally those plantlets were acclimatized in field. Thus a protocol was established for rapid micropropagation of this medicinal plant through induction of direct and indirect organogenesis from nodal explant. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13401 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):01-09, 2008